Finding Solace Behind Bars: Experiences of Inmates in Kumasi Central Prison - Ofori-Dua, Kwadwo; Forkuor, John Boulard; Onzaberigu, Nachinaab John (Journal of victimology and victim justice (Print), 2020)
Most studies on prisoners in West Africa and Ghana have been on prisoners’ rehabilitation services and overcrowding conditions of inmates. This study sought to explore how inmates find solace while in prison given the poor prison conditions reported in many studies in developing countries. It aimed, among others, to examine the activities or things that give solace and happiness within the prison environment as well as the strategies inmates adopt to sooth their conditions in prison. Qualitative approaches were adopted in the study. Data were collected mainly through the use of interviews. The study involved a sample size of 31 male inmates within the Kumasi Central Prison. It was found that inmates form social networks in the cell to find peace (solace) and relief in prison cells. They also engage in indoor games, religious activities and skills training as ways of coping with the harsh conditions. It was also found that family network and support were central to inmates’ solace in prison custody. Survival and finding solace in cell were also dependent on the kind of friendship support inmates acquire in the prison.